CENTRALIZED MANAGEMENT OF FIDUCIARY DEED MAKING AND REGISTRATION BY ABC & PARTNERS (ABC-P) LAW FIRM (FIDUCIARY CENTRALIZATION) - Rayhan Arif Hadi Pratama; David Maruhum Lumban Tobing (Jurnal Ilmiah Advokasi, 2024)
A notary who works under a Fiduciary Guarantee Deed which is made centrally will be suspected and indicated of committing a violation, which will have legal consequences and affect the evidentiary strength of the deed. This research focuses on the centralized legal impact of making a Fiduciary Guarantee Deed, the legal impact of registering a Fiduciary Guarantee Deed made by a notary that is registered by a notary, and how to overcome this legal impact. This research uses normative juridical law. The research results show that because the Fiduciary Guarantee Deed is made in a centralized manner, violations of the Notary Position Law, Fiduciary Guarantee Law, Notary Code of Ethics, and INI DKP No. 1 of 2017 can cause the Fiduciary Guarantee Deed to be degraded into a private deed or null and void by law. Every Fiduciary Certified Guarantee issued from the registration of a Fiduciary Guarantee Deed carried out by a Notary must be declared legally void. The Ministry of Law and Human Rights handles the creation of Fiduciary Guarantee Deeds centrally by encouraging non-bank financial institutions to use notary services in the regions. There are no Financial Services Authority regulations that prohibit fiduciary centralization. The Central Notary Supervisory Council is responsible for making fiduciary guarantee deeds by carrying out inspections, coaching notaries through advice, consultation and outreach so that they do not make deeds that exceed the reasonable limits of deeds that indicate suspected violations. The Central Council of Notaries is also responsible for supervising the drafting and drafting of Ministerial Regulations together with the Minister of Law and Human Rights. Keywords: Centralization; Fiduciary Guarantee Deed; Online registration